Minimal Invasive Pericardial Perfusion Model in Swine: A Translational Model for Cardiac Remodeling After Ischemia/Reperfusion Injury - Marek-Iannucci, Stefanie; Thomas, Amandine; Gottlieb, Roberta A. (Frontiers in Physiology, 2020)
Rationale: Adverse remodeling leads to heart failure after myocardial infarction, with important impact on morbidity and mortality. New therapeutic approaches are needed to further improve and broaden heart failure therapy. We established a minimally invasive, reproducible pericardial irrigation model in swine, as a translational model to study the impact of temperature on adverse cardiac remodeling and its molecular mechanisms after myocardial infarction. Objective: Chronic heart failure remains a leading cause of death in western industrialized countries, with a tremendous economic impact on the health care system. Previously, many studies have investigated mechanisms to reduce infarct size after ischemia/reperfusion injury, including therapeutic hypothermia. Nonetheless, the molecular mechanisms of adverse remodeling after myocardial infarction remain poorly understood. By deciphering the latter, new therapeutic strategies can be developed to not only reduce rehospitalization of heart failure patients but also reduce or prevent adverse remodeling in the first place. Methods and Results: After 90 minutes of myocardial infarction, a 12Fr dual lumen dialysis catheter was place into the pericardium via minimal invasive, sub-xiphoidal percutaneous puncture. We performed pericardial irrigation with cold or warm saline for 60 minutes in 25 female farm pigs after ischemia and reperfusion. After one week of survival the heart was harvested for further studies. After cold pericardial irrigation we observed a significant decrease of systemic body temperature measured with a rectal probe in the cold group, reflecting that the heart was chilled throughout its entire thickness. The temperature remained stable in the control group during the procedure. We did not see any difference in arrhythmia or hemodynamic stability between both groups. Conclusions: We established a minimally invasive, reproducible and translational model of pericardial irrigation in swine. This method enables the investigation of mechanisms involved in myocardial adverse remodeling after ischemia/reperfusion injury in the future.